PERILAKU ORANG TUA DALAM MEMBERIKAN MAKANAN BERSERAT PADA SISWA SEKOLAH DASAR - Eka Putranti Meiliana Sari (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2018)
This study aimed to describe parents’ behavior in givingfiber foods. Type of this study was a descrtiptive research.Research object was behavior in concuming fiber foods,the research subject was the students of SD Negeri SawahGirisekar Panggang Gunungkidul, and the source data wasstudents’ parents of SD Negeri Sawah Girisekar PanggangGunungkidul. Data collection methods used questionaires.Data analysis technique used a descriptive and quantitativeanalysis to descrube the category of the variable. This studyshows that the parents’ behavior in giving fiber foods ofthe students of SD Negeri Sawah Girisekar PanggangGunungkidul was in enough category with the relativefrequency 45.59%. It means that students’ parents weregood enough in giving fiber foods. From the indicatorsconcisted of knowledge, attitude, and action show also inenough category. Indicator of knowledge in concuming fiberfoods was in enough category with the relative frequency55.88%. The indicator of attitude in concuming fiberfoods was in enough category with the relative frequency38.24%. Indicator of action in concuming fiber foods wasin enough category with the relative frequency 61.76%.